2020
DOI: 10.1136/gpsych-2019-100181
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid psoriasis-bipolar disorder successfully treated with apremilast: much more than a mere coincidence?

Abstract: Psoriasis is a chronic, immune mediated, systemic inflammatory skin disease with a reported prevalence of 0.6%–4.8% in the general population. Bipolar disorder (BP) is a severe episodic psychiatric disorder that ranks as the fourth leading cause of disability. Recent evidence suggests that genetic and immunological factors play a significant role in the development of both disorders. Studies have also shown a higher association of psychiatric disorders among patients with psoriasis. Moreover, several autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, many biologics (adalimumab, certolizumab pegol, etanercept, infliximab, ustekinumab, guselkumab, risankizumab, brodalumab, secukinumab, ixekizumab) can be used in patients receiving highly active antiretroviral therapy (HAART) and having undetectable viral load [19]. In case of detectable Cohen-Sors 2021 [13] Hematologic malignancy: 10 Gottlieb 2021 [36] Kahn 2019 [37] Nagata 2019 [38] Uvais 2020 [39] Vico-Alonso 2020 [40] Melis 2020 [41] Perrone 2017…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many biologics (adalimumab, certolizumab pegol, etanercept, infliximab, ustekinumab, guselkumab, risankizumab, brodalumab, secukinumab, ixekizumab) can be used in patients receiving highly active antiretroviral therapy (HAART) and having undetectable viral load [19]. In case of detectable Cohen-Sors 2021 [13] Hematologic malignancy: 10 Gottlieb 2021 [36] Kahn 2019 [37] Nagata 2019 [38] Uvais 2020 [39] Vico-Alonso 2020 [40] Melis 2020 [41] Perrone 2017…”
Section: Discussionmentioning
confidence: 99%
“…Even the association between parental common mental disorders (anxiety and depression) and offspring's risk of psoriasis has been determined [ 165 ]. Another study reported a woman with bipolar disorder subsequently developed psoriasis and experienced exacerbations in psoriatic lesions during each manic episode [ 166 ]. In accordance with the clinically elevated psoriatic inflammation in patients with autistic spectrum disorder, Nadeem et al reported a high level of systemic inflammation in autistic mouse models, suggesting the link between autism and psoriasis activity [ 167 ].…”
Section: Psychological Stress and Other Mental Disordersmentioning
confidence: 99%